Liquidity, insolvency and the state - Dirk H. Ehnts (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
The importance of liquidity and insolvency for nation states and banks has been highlighted by current economic woes in the eurozone and elsewhere. The concepts are grounded in monetary theory, which determine the way they are interpreted. Connected to the discussion of autometallism and Chartalism in the early 20th century, monetary economists of today have come full circle. Discussing some modern authors, it is argued that the concepts of liquidity and insolvency are connected. However, if the central bank functions as lender of last resort the link is cut. Also, fiscal policy has the potential to remove problems of illiquidity and insolvency in the financial system. Illiquidity and insolvency are signals of stress in the real economy. Their oppression through central bank policy might lead to the (wrong) perception that all is well in the economy.
Keywords: E5; E6; G21; 330; monetary policy; fiscal policy; balance sheets; autometallism; Chartalism